A timeseries analysis of the impact of foreign aid on central government's fiscal budget in Uganda - Thomas Bwire; Oliver Morrissey; Tim Lloyd (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
A dynamic relationship between foreign aid and domestic fiscal variables in Uganda is analysed using a cointegrated vector autoregressive model over the period 1972-2008. Results show that aid is a significant element of long-run fiscal equilibrium, is associated with increased tax effort and public spending, and reduced domestic borrowing. Shocks to tax revenue are the pulling forces, while those to domestic borrowing, government spending and aid are the pushing forces of the system. In terms of policy, it is crucial for donors to increase the reliability and predictability of aid, coordinate aid delivery systems and also make aid more transparent.
Keywords: C32; F35; O23; O55; 330; domestic fiscal variables; aid; economic instability; ESAP; CVAR; common trends; Uganda